Analisis Perbandingan Pendapatan Dan Difusi Inovasi Pertanian Padi Organik Di Desa Damarwulan Kecamatan Kepung Kabupaten Kediri - Khusnaini, Hijriyatul; Riana, Fitria Dina; Pratiwi, Destyana Ellingga; Setiawan, Budi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Agricultural development at this time apart from pursuing high production also began to pay attention to environmental conditions. The direction of agricultural development in Indonesia is towards sustainable development (Sustainable Development Goals (SDG's)). The target of sustainable agricultural development is changes in economic conditions, welfare, social society, and attention to natural conditions. Organic farming is introduced to farmers to support sustainable agricultural development goals. However in practice, there are still a few farmers who are interested in organic rice cultivation. So it is necessary to know the ratio of income earned by inorganic and organic rice farmers and it is necessary to know what factors are considered by farmers in choosing rice cultivation methods both inorganic and organic. The research method used in this study is the method of farming analysis, T test, and logistic regression. The results of the farming analysis show that the income of inorganic rice farmers is IDR 2,600,873 and that of organic rice farmers is IDR 8,263,688. Based on the results of the T-test, it was found that there was a significant difference in income between the income of inorganic rice farmers and the income of organic rice farmers. Logistic regression carried out resulted in significant factors considered by farmers, namely relative advantage, suitability with culture, complexity in organic farming cultivation, and age of farmers. Based on the test results, it can be concluded that there is a significant difference in income between inorganic rice farmers and organic rice farmers. Factors considered by farmers in choosing inorganic and organic rice cultivation methods are relative advantages, suitability with culture, complexity in organic farming cultivation, and age of farmers